Impact of Probiotic Swamp Bacteria on the Prevention of Aeromonas hydrophila Infection in Striped Snakehead (Channa striata) - Wijayanti, Marini; Sasanti, Ade Dwi; Jubaedah, Dade; Citra, Nyayu (Journal of Fish Health, 2025)
Probiotics are microbes that can modify the bacterial structure in fish digestive systems. Probiotics are used as feed additives and can improve the host's health. As a result, it can help to prevent Aeromonas infection. This study aims to determine the effectiveness of bacteria from the swamp (Bacillus sp. and Streptomyces sp.) on feed in preventing Aeromonas hydrophila infection in striped snakeheads. The study used P0 (control), P1 (Bacillus sp.), P2 (Streptomyces sp.), P3 (Bacillus sp. and Streptomyces sp. combination), each bacterium 10 ml kg-1 feed. Total of bacteria, prevalence, fish growth, survival rate, and water quality are among the variables assessed. The fish survival, fish growth, and feed efficiency in Channa treated with a combination of Bacillus and Streptomyces (P3) were significantly highest among other, resulting of best prevalence 2.38%.